The Influence Of Deviant Workplace Behavior And Work Commitment On Millennial Employee Performance With The Implementation Of Anti-Fraud Strategies As A Mediating Variable In Pt Permodalan Nasional Madani - Andini Ayu Larasati; Deden Kurniawan (Politeknik Siber Cerdika Internasional, 2023)
The future of Indonesia is determined by the quality of human resources, especially the millennial generation. In the context of facing the problem of fraud cases in Indonesia, of course we hope that the millennial generation is relatively more sterile from permissive values towards fraud behavior. A negative work environment (deviant workplace behavior) can affect employee performance in an organization. Fraudulent behavior will have an impact on the poor performance of millennial employees. This can also affect organizational performance in a company. Survey fraud conducted by AFCE (2019), that the biggest fraud perpetrators were employees with a percentage of 31.8% and 20% with an age group of 20 - 35 years. This means that most fraud perpetrators come from the millennial age group. This study aims to analyze the effect of deviant workplace behavior and work commitment on millennial employees with the implementation of anti-fraud strategies as a mediating variable at Permodalan Nasional Madani. This study uses quantitative research methods and this research data is taken using purposive sampling, meaning that the sample is based on certain characteristics, traits or characteristics. The number of samples in this study were 140 millennial employees at PT Permodalan Nasional Madani. The results showed that the performance of millennial employees has a significant effect on deviant workplace behavior and work commitment through the implementation of anti-fraud strategies.